(3fUGH GdGMJSGHs - (3GdSfGej, YeQ Hf eMeO YhV, J (B696 (3g`s ((3YKeGf Hf eUdM GdOjf GdMejOjs)
(3ChdgG (B:s
(3HYO GdHSedI ; GdMeO ddg GdMSjH GdQbjH Ydi fhGdg LeY YHOg YeQ Hf eMeO Hf YhV GdSfGej aj JUfja gPG GdcJGH hgh fSGH GdGMJSGH eSGFd GNJUJ HGdfSHI Edi MSH efUH GdMSHIs
(3BNQgG (B:s
(3GdLhGH fYe dCf YeQ QVj Gddg Yfg CNQL CNJ CHj HcQ QVj Gddg JYGdi Yfg ef HjJg Mjf fGMJ Ydjg ef UMjM GdHNGQjs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B5 / 63s
(3eYLe GdeDdajf (B2 / 577s
(3cTa GdXfhf (B2 / 1953s
(3TPQGJ GdPgH (B5 / 436s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3Gdabg GdMfHdjs